Evaluation of hard gelatin capsules and hydroxypropyl methylcellulose containing ampicillin - Graziella Gonçalves Weigert (Química Nova, 2012)
This study aims to develop and evaluate formulations containing ampicillin in capsules of gelatin and hydroxypropyl methylcellulose (HPMC). Two formulations (A and B) were developed. The final product quality was evaluated by testing for quality control and the results were in agreement with the Brazilian Pharmacopoeia. The formulations with HPMC capsules showed lower percentages of drug dissolved (99.67%, HPMC-A and 87.70%, HPMC-B) than the gelatin (100.18%, GEL-A and 101.16% GEL-B). Because of the delay of the ampicillin release observed in the dissolution profiles, it becomes necessary to evaluate the drugs that can be conditioned in the HPMC capsules.